1999
DOI: 10.1091/mbc.10.4.1093
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocathechin-3 Gallate Selectively Inhibits the PDGF-BB–induced Intracellular Signaling Transduction Pathway in Vascular Smooth Muscle Cells and Inhibits Transformation ofsis-transfected NIH 3T3 Fibroblasts and Human Glioblastoma Cells (A172)

Abstract: Enhanced activity of receptor tyrosine kinases such as the PDGF ␤-receptor and EGF receptor has been implicated as a contributing factor in the development of malignant and nonmalignant proliferative diseases such as cancer and atherosclerosis. Several epidemiological studies suggest that green tea may prevent the development of cancer and atherosclerosis. One of the major constituents of green tea is the polyphenol epigallocathechin-3 gallate (EGCG). In an attempt to offer a possible explanation for the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 30 publications
6
95
0
Order By: Relevance
“…Baicalin belongs to a class of polyphenols. Previous studies have shown that polyphenols inhibit PDGFRβ autophosphorylation [19][20][21][22]. Although the mechanisms underlying the inhibitory effect of these polyphenols remain to be established, previous studies suggested that some of these molecules may inhibit the activation of receptor tyrosine kinase by competing with adenosine triphosphate for binding to the kinase domain of the receptor, resulting in impaired activation of key signaling intermediates [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin belongs to a class of polyphenols. Previous studies have shown that polyphenols inhibit PDGFRβ autophosphorylation [19][20][21][22]. Although the mechanisms underlying the inhibitory effect of these polyphenols remain to be established, previous studies suggested that some of these molecules may inhibit the activation of receptor tyrosine kinase by competing with adenosine triphosphate for binding to the kinase domain of the receptor, resulting in impaired activation of key signaling intermediates [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG is reported to affect many different signal transduction pathways, including inhibition of various protein kinases, suppression of the activation of transcription factors such as AP-1 and NFκB, blockade of growth receptormediated pathways, and induction of cell cycle arrest or apoptosis (15)(16)(17)(18). EGCG was also found to attenuate growth factor-mediated proliferation, inhibit cell transformation, and repress angiogenesis in various cancer models (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…EGCG, the most abundant polyphenol in green tea, has been shown to inhibit cell proliferation (Asano et al, 1997) and induce apoptosis (Hibasami et al, 1998;Paschka et al, 1998) in tumour cells. Other means by which EGCG may prevent cancer include its inhibition of urokinase activity (Jankun et al, 1997), mitogen-activated protein kinases (MAPKs) activation (Jankun et al, 1997;Ahn et al, 1999), lipooxygenase and cyclooxygenase activities (Stoner and Mukhtar, 1995), and arrest of the cell cycle (Ahmad et al, 1997;Fujiki et al, 1998) in tumour cells.…”
mentioning
confidence: 99%